The development of À La Carte-based blended learning for EFL speaking skills / Wang Hanxu ... [et al.] - Wang, Hanxu; Ismail, Irwan Mahazir; Zheng, Zheng; Khamis, Nor Yazi (Universiti Teknologi MARA, Kedah, 2023)
Information and communication technology development has called for blended learning to expand the quality of higher education. During the Covid-19 pandemic, education institutions worldwide shifted to blended learning to meet the challenge. Nevertheless, like any disruptive innovations in their early stage, blended learning faced unsatisfied outcomes, especially in English-speaking courses in Chinese colleges. The current blended learning model remains in a traditional teacher-center, bottom-up order, emphasizing rote memorization that has little relevance to the students, thus hindering students’ learning motivation and self-efficacy. The big class size has also caused overload tasks to the teachers who have insufficient experiences and specific knowledge and skills to tackle the issue. The study offers the development of an innovative blended learning model in the form of À la Carte to facilitate English-speaking skills learning and teaching. The aim is to determine the innovation's effectiveness in enhancing EFL students’ motivation and self-efficacy in learning English-speaking skills. The study adopted two credible theories, namely social cognitive theory, and self-determination theory; four source models of self-efficacy, self-determination theory and Keller’s ARCS model were used to guide the development. It resulted in six practical principles used to guide the development of lesson plans of ÀLC-based blended learning for an English-speaking skills lesson for Cangzhou Technical College students. A quasi-experimental research design was conducted to investigate the effectiveness of the ÀLC model using 70 first-year students from two classes, ÀLC-based blended learning (experimental group) and existing blended learning at CTC (control group). Findings indicated significant differences between the two groups’ motivation and self-efficacy. The developed theoretical framework and the ÀLC-based blended learning lesson plan were appropriate and feasible to improve students’ motivation and self-efficacy in learning the language.